The Influence Of Operational Strategy And Operational Competence On Quality Culture And Quality Of Hospital Services And Implications On Patient Satisfaction (Survey At Rapha Theresia Hospital, Baiturrahim Hospital, Arafah Islamic Hospital And Mitra Hospital In Jambi Province) - Renaldus Iwan Sumarta; Iman Sudirman; M. Sidik Priadana; Atty Tri Juniarti (STMIK Dharma Wacana, 2024)
This research aims to identify the influence of operational strategy on operational competence on quality culture, quality of hospital services, and patient satisfaction. According to the Health Law (UU No. 17 of 2023), improving the quality of hospital services in Indonesia is very important to reduce wastage of foreign exchange due to people taking care abroad. This examination was carried out at hospitals in Jambi Province (Rapha Theresia Hospital, Baiturrahim Hospital, Arafah Islam Hospital, Mitra Hospital) using a quantitative approach. Data was collected through interviews, questionnaires, and observations from 300 employees and distributed to each hospital. The results of the analysis show that operational strategies and operational competencies in food have a significant influence on quality culture, service has a 69.30% influence. This, operational strategy and operational competency and food have a significant influence on the quality of hospital services (74.48%). Good quality culture and the quality of hospital services simultaneously have a significant influence on patient satisfaction and a total influence of 81.52%. There are still practical suggestions for hospitals to improve operational strategies, develop operational competence, strengthen quality culture, and improve service quality to improve patient satisfaction. The authors also asked about the panalungtikan salajengna kalayan ngalibetkeun additional variables jeung negligent the scope of the panalungtikan to the city/district séjén pikeun add to the results of the panalungtikan.